A Convenient Palladium‐Catalyzed Reductive Carbonylation of Aryl Iodides with Dual Role of Formic Acid. Issue 17 (2nd March 2016) - Qi, Xinxin; Li, Chong‐Liang; Wu, Xiao‐Feng
Abstract: Palladium‐catalyzed reductive carbonylation of aryl halides represents a straightforward pathway for the synthesis of aromatic aldehydes. The known reductive carbonylation procedures either require CO gas or complexed compounds as CO sources. In this communication, we developed a palladium‐catalyzed reductive carbonylation of aryl iodides with formic acid as the formyl source. As a convenient, practical, and environmental friendly methodology, no additional silane or H2 was required. A variety of aromatic aldehydes were isolated in moderate to excellent yields under mild reaction conditions. Notably, this is the first procedure on using formic acid as the formyl source. Abstract : Say no to CO gas ! A convenient, practical, and environmental friendly palladium‐catalyzed reductive carbonylation of aryl iodides with formic acid as the formyl source has been developed (see scheme). No additional silane or H2 was required here. A variety of aromatic aldehydes were isolated in moderate to excellent yields under mild reaction conditions.